2021
DOI: 10.3390/diagnostics11030571
|View full text |Cite
|
Sign up to set email alerts
|

Oral Diagnostic Methods for the Detection of Periodontal Disease

Abstract: Periodontitis is a common immune-inflammatory oral disease. Early detection plays an important role in its prevention and progression. Saliva is a reliable medium that mirrors periodontal health and is easily obtainable for identifying periodontal biomarkers in point-of-care diagnostics. The aim of this study is to evaluate the effectiveness of diagnostic salivary tests to determine periodontal status. Whole saliva (stimulated/unstimulated) from twenty healthy and twenty stage III grade B generalized periodont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 49 publications
1
16
0
2
Order By: Relevance
“…Dhanya et al [ 31 ] found that the salivary glucose level collected under unstimulated settings is higher than that collected under stimulated conditions, which is compatible with the findings of this study. Other investigations have demonstrated that the salivary glucose level collected under unstimulated and stimulated settings does not significantly differ [ 39 ]. Because individuals may not readily accept stimulation and stimulated saliva contains more water than unstimulated saliva, unstimulated saliva may be a better indicator of normal physiological condition.…”
Section: Discussionmentioning
confidence: 99%
“…Dhanya et al [ 31 ] found that the salivary glucose level collected under unstimulated settings is higher than that collected under stimulated conditions, which is compatible with the findings of this study. Other investigations have demonstrated that the salivary glucose level collected under unstimulated and stimulated settings does not significantly differ [ 39 ]. Because individuals may not readily accept stimulation and stimulated saliva contains more water than unstimulated saliva, unstimulated saliva may be a better indicator of normal physiological condition.…”
Section: Discussionmentioning
confidence: 99%
“…Those data indicated that elevation of salivary lactoferrin is associated with lymphocytic infiltration on salivary glands and the immune imbalance that occurs in SS. However, salivary lactoferrin levels had been elevated in other conditions, such as periodontitis and SLE, suggesting a lack of specificity for biomarkers for SS [ 38 , 39 ].…”
Section: Salivary Biomarkers Of Sjogren’s Syndromementioning
confidence: 99%
“…The diagnosis process is complex, time consuming, and based on manual periodontal probing, which is operator dependent [ 3 , 4 , 5 , 6 ] and on radiological investigations, which are invasive and provide a lack of soft tissue contrast [ 7 , 8 , 9 , 10 ]. Other investigations that may add value to the diagnosis process are periodontal biomarker analysis [ 11 ] and microbiological analysis [ 12 , 13 , 14 ]. Due to the evolution of technology, periodontal tissue imaging has started to play a key role in periodontal disease diagnosis.…”
Section: Introductionmentioning
confidence: 99%